Implementation of Jurisprudential Inquiry Model to Improve Social Skills and Learning Outcomes of Elementary School - Suryadi Hasyda; Ahmad Yani; Uslan Uslan (UM Purwokerto Press, 2023)
The study on the implementation of the Jurisprudential Inquiry Model (JIM) has been conducted at SDN Naioni 1, Kupang, Indonesia. This study will describe the model for implementing JIM to improve social skills and student learning outcomes using the classroom action research method following the McTaggart and Kemmis models on the 29 students. As a result, cycle I showed an increasing value of 2.57% to 3.33% in the sufficient and good categories, respectively. On the other hand, the social skills of students in social studies learning during the learning process showed an increasing value of 2.54% to 3.45% with good and outstanding categories, respectively. These results also affect the Minimum Completeness Criteria in cycle II. In conclusion, we propose implementing the jurisprudential inquiry model to improve fourth-grade students' social skills and learning outcomes at SD Negeri 1 Naioni Kota Kupang.